(untitled) (Faridpur Medical College Journal, 2016)
Dacryocystorhinostomy (DCR) is a bypass surgery in which an anastomosis is made between the medial wall of the lacrimal sac & the lateral wall of the nasal mucosa by cutting the intervening bone at the level of middle meatus to restore the flow of tears when the obstruction is beyond the common canaliculus. The only successful treatment of chronic dacryocystitis is DCR. The aim of this study was to evaluate the surgical intervention of conventional external DCR without silicon tube intubation. This prospective study was conducted at General Hospital, Faridpur from July 2012 to June 2014. Eighty cases with chronic dacryocystitis were selected for the study. We excluded the patients with lacrimal fistula, failed DCR and gross nasal pathology like deviated nasal septum, grossly hypertrophied inferior turbinate, atrophic rhinitis, nasal tumour, and polyp from our study. The patients’ mean age at the time of surgery was 41.9±8.1 years ranged from 30 to 60 years. The operation was done under local anaesthesia by applying same technique. Then the patients were followed up for 12 months. In this study, we observed recurrence in five patients (6.25%) and complications from DCR are infrequent and not sight threatening. There were seven patients with reactionary haemorrhage, one wound infection, three wound gap, two epicanthal fold, one granuloma formation and five failed DCR. The success rate is 93.75% who underwent external DCR for the management of epiphora due to nasolacrimal duct obstruction. Faridpur Med. Coll. J. Jan 2015;10(1): 20-22